Supply chain leadership : developing a people-centric approach to effective supply chain management - Robertson, Peter W. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Supply Chain leaders are key to achieving sustainable supply chain excellence and long-term competitive advantage. This book addresses 'big-picture' supply chain leadership and provides a roadmap and practical advice to help Supply Chain leaders successfully navigate this challenging social and technical environment. The book describes crucial leadership characteristics and explains the actions necessary to develop and appraise the skills in both new and existing leaders. It presents a socio-technical framework, which includes the key aspects of supply chain relationships, the supply chain business environment, overall supply chain competitiveness, supply chain sustainability, and supply chain risks. The book works through the recruitment, training and development of leaders as well as obstacles and risks, to offer a fresh, people-centred approach. Pedagogy to aid learning is incorporated throughout, including an introduction to each chapter explaining the key learnings; tables, diagrams and equations to help visualise the concepts and methods covered; real-life case studies and examples; and end of chapter review questions and assignment tasks. This textbook should be essential reading for Advanced Undergraduate and Postgraduate students of Supply Chain, Logistics and Operations Management. The practice-based and applied approach also makes it valuable for operating Supply Chain leaders and those studying for professional qualifications. Online resources include chapter-by-chapter PowerPoint slides, a test bank of exam questions, and suggested tutorial topics"--
OCLC-licensed vendor bibliographic record.
Keywords: Business logistics; Leadership; Strategic planning; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Human Resources & Personnel Management